A smart metering for energy management system via GSM-SMS based protocol - Fakharuddin, Azhar (2011)
Energy resources and their management is one of the prime challenges to world especially developing countries like Malaysia where the significant contribution to energy generation is based on imported resources. In the mean time the elasticity curve is having a reasonable difference between growing demand and installation capacity. A study of local electricity structure shows that the individual user's consumption pattern is not a responsible one which leaves opportunity for policy makers to introduce new habit formation programmes like variable time pricing etc. This research model helps to create a better understanding and awareness towards the value and the importance of electrical energy, energy saving, promoting of smart energy management as well as an innovation towards further improvement to proven existing system. In this research a brief description about smart metering and the trends in meters from 'traditional' to 'smart' is provided. Feedback and its affect on a consumer's habit formation is a focus of literature. The system design consists of a cellular based power monitoring system using SMS protocol for data transmission. The designed system is compatible with all type of existing monitoring setups at consumer's end. The proposed monitoring system consist of a new energy calculation algorithm, offering electricity packages with a intelligent monitoring for daily power consumption connected to base-station via GSM network. In addition, the prototype designed aims to monitor the consumption records, send it periodically to the server to update to the relevant user profile, provide feedback alerts to the consumer on demand and also provide a better control to utility over individual user. With this proposed methodology, the end users are provided with proper awareness and they may plan their electrical consumption pattern. User are given plenty and incentives based on different time and consumption volume factors thus peak power consumption can be reduced and also wastage of electricity can be reduced until a specific level. The designed prototype proved to be a real-time and effective in individual data collection. It proved to be error free when compared to a manual metering data collection process. One of the most interesting features of the designed module "GSM-PRO" is that it doesn't need any replacement in currently existing monitoring systems. The intelligent pulse reading section of the meter made it compatible with both type of metering systems either it is an electromechanical meter or electronic one. is also provided a wider control to utility over individual user in case of any fraud monitoring or supply interruption.